Peran Media Sosial Instagram @Plnup3surabayaselatan sebagai Media Promosi Produk dan Edukasi Kelistrikan dalam Menarik Minat Beli Pelanggan PT PLN (PERSERO) UP3 Surabaya Selatan - Syahrani, Ananda Rizkiah; Andarini, Sonja (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
The use of social media as a promotional and educational tools is increasingly important in company marketing strategies in the current digital era. This research examines the role of social media Instagram account @plnup3surabayaselatan in supporting product promotion and electrical education to attract buying interest from PT customers. PLN (Persero) UP3 South Surabaya. This research method uses a qualitative approach with data collection techniques through observation and interviews with customers and employees of PLN UP3 South Surabaya as well as content analysis of related posts. Research findings show that Instagram account @plnup3surabayaselatan is less effective in increasing customer awareness about electrical products and services offered by PT PLN (Persero) UP3 South Surabaya. Apart from that, the educational content presented is also less prominent so that the efficient and safe use of electrical energy is not yet fully understood by customers and the wider community. The results of this research provide important insights for companies in designing marketing strategies via social media to increase customer engagement and expand market share in today's digital era.